Complexity-entropy maps as a tool for the characterization of the clinical electrophysiological evolution of patients under pharmacological treatment with psychotropic drugs - Díaz López, Juan Manuel; Mateos, Diego Martín; Boyallián, Carina (2025)
Fil: Díaz López, Juan Manuel. Instituto Argentino de Ciencias de la Conducta; Argentina.